2014
DOI: 10.1200/jco.2013.50.4357
|View full text |Cite|
|
Sign up to set email alerts
|

Clinical Utility of a Plasma-Based miRNA Signature Classifier Within Computed Tomography Lung Cancer Screening: A Correlative MILD Trial Study

Abstract: A B S T R A C T PurposeRecent screening trial results indicate that low-dose computed tomography (LDCT) reduces lung cancer mortality in high-risk patients. However, high false-positive rates, costs, and potential harms highlight the need for complementary biomarkers. The diagnostic performance of a noninvasive plasma microRNA signature classifier (MSC) was retrospectively evaluated in samples prospectively collected from smokers within the randomized Multicenter Italian Lung Detection (MILD) trial. Patients a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
355
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 380 publications
(366 citation statements)
references
References 23 publications
9
355
0
2
Order By: Relevance
“…• Selection of miRNA with significantly altered expression as potential biomarkers performance of plasma microRNAs as complementary biomarkers for LDCT screening in a cohort of current or former smokers, older than 50 years [6]. They retrospectively evaluated plasma miRNA signatures in samples from 939 participants, including 69 patients with lung cancer and 870 diseasefree individuals.…”
Section: Methods Of Mirna Expression Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…• Selection of miRNA with significantly altered expression as potential biomarkers performance of plasma microRNAs as complementary biomarkers for LDCT screening in a cohort of current or former smokers, older than 50 years [6]. They retrospectively evaluated plasma miRNA signatures in samples from 939 participants, including 69 patients with lung cancer and 870 diseasefree individuals.…”
Section: Methods Of Mirna Expression Analysismentioning
confidence: 99%
“…However, a high rate of false positive results associated with LDCT screening opened a debate over the cost-effectiveness of LDCT screening programs and the potential harms related to overdiagnosis and radiation-induced cancers. In view of personalised medicine, the potential role for specific, miRNAbased biomarkers to complement the radiological modalities and increase the total sensitivity and specificity of the lung cancer screening process is currently being investigated [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Boeri et al recently validated their miRNA signature in a large cohort of individuals with lung cancer [26], highlighting the potential for application in other cancers. We adopted this method to overcome the limitations associated with global normalization approaches.…”
Section: Discussionmentioning
confidence: 99%
“…The incremental number of invasive procedures is quite low, although additional diagnostic ct imaging is more frequent. A recent report on the use of a biomarker-a plasma-based microrna signature classifier-during the mild ldct screening trial 34 demonstrated that the combination of the microrna signature classifier and ldct reduced the false-positive rate to 3.7% 43 . If a microrna signature classifier or another biomarker is confirmed to be effective in reducing false-positive screen rates, it would, in many cases, avoid the need for follow-up ct imaging and unnecessary invasive procedures and would reduce costs.…”
Section: Discussionmentioning
confidence: 99%